Catch composition of non-motorised and motorised traditional fishing crafts in Andhra Pradesh - Myla S, Chakravarty; G, Venkata Raju; G R C, Ganesh (Indian Journal of Fisheries, 2016)
The fishing practices of the traditional sector along Andhra Pradesh coast have changed significantly due to motorisation of fishing crafts. The comparison of the landings and values realised indicate that motorised crafts are able to target high valued fishes from distant waters. However, non-motorised boats fish in the near-shore waters operating trammel nets. The study on gear and quantity/value- based fish catch composition indicates the diversified fishing practices along Andhra coast and change in the catch composition between the non-motorised and motorised traditional fishing boats.